What Is Regenerative Agriculture? A Review of Scholar and Practitioner Definitions Based on Processes and Outcomes - Newton, Peter; Civita, Nicole; Frankel-Goldwater, Lee; Bartel, Katharine; Johns, Colleen (Frontiers in Sustainable Food Systems, 2020)
Regenerative agriculture is an alternative means of producing food that, its advocates claim, may have lower—or even net positive—environmental and/or social impacts. Regenerative agriculture has recently received significant attention from producers, retailers, researchers, and consumers, as well as politicians and the mainstream media. Despite widespread interest in regenerative agriculture, no legal or regulatory definition of the term “regenerative agriculture” exists nor has a widely accepted definition emerged in common usage. This paper answers the research question: How have different scholars and practitioners defined regenerative agriculture? We reviewed 229 journal articles and 25 practitioner websites to characterize the term “regenerative agriculture.” Our review revealed that there were many definitions and descriptions of regenerative agriculture in usage. These were variously based on processes (e.g., use of cover crops, the integration of livestock, and reducing or eliminating tillage), outcomes (e.g., to improve soil health, to sequester carbon, and to increase biodiversity), or combinations of the two. Process-based definitions may imply that advocates or users of such definitions are open-minded about the possible outcomes of these processes. Similarly, outcome-based definitions may imply that users of such definitions are open-minded about the processes that may lead to those outcomes. We discuss the implications of these different forms of definition for policy, including for certification programs and for payments for carbon sequestration programs. More generally, wide variance in the definitions used may lead to uncertainty about what different actors mean when they talk about regenerative agriculture. We suggest that it may be helpful for individual users of the term “regenerative agriculture” to define it comprehensively for their own purpose and context.